Characterization of Portuguese Centenarian Eating Habits, Nutritional Biomarkers, and Cardiovascular Risk: A Case Control Study. (13th March 2018) - da Silva, A. Pereira; Valente, A.; Chaves, C.; Matos, A.; Gil, A.; Santos, A. C.; Gorjão-Clara, J. P.; Bicho, M.
Abstract : Background and Aims . Eating habits may contribute to longevity. We characterized the eating habits and cardiovascular risk (CVR) biomarkers in Portuguese centenarians (CENT) compared to controls. Methods and Results . Centenarians (n = 253 ), 100.26 ± 1.98 years, were compared with 268 controls (67.51 ± 3.25), low (LCR) and high (HCR) CVR (QRISK®2-2016). Anthropometric and body composition were evaluated by bioimpedance. Abdominal obesity, BMI, and fat mass (FM) cut-offs were according to the WHO. Sarcopenia was defined by muscle mass index cut-off ≤ 16.7 kg/m 2 . Daily red meat intake, adjusted for age and gender, was sarcopenia protective (OR = 0.25, 95% CI = 0.096–0.670, P = 0.006 ); however, it contributes for FM excess (OR = 4.946, 95% CI = 1.471–16.626, P = 0.01 ), overweight, and obesity (OR = 4.804, 95% CI = 1.666–13.851, P = 0.004 ). This centenarian eating habit (2%) contrasts to HCR (64.3%). The history of red meat (P < 0.0001 ) and canned/industrialized food intakes (P < 0.0001 ) was associated with HCR. Basal metabolism was lower in centenarians versus LCR/HCR (CENT = 1176.78 ± 201.98; LCR = 1356.54 ± 170.65; HCR = 1561.33 ± 267.85; P < 0.0001 ), BMI (CENT = 21.06 ± 3.68; LCR = 28.49 ± 4.69; HCR = 29.56 ± 5.26; P < 0.0001 ), waist circumference (CENT = 85.29 ± 10.83; LCR = 96.02 ± 11.71; HCR = 104.50 ± 11.84; P < 0.0001 ), and waist-hip ratio (CENT = 0.88 ± 0.07; LCR = 0.92 ± 0.08; HCR = 1.01 ± 0.08; P < 0.0001 ). CENT had lower total cholesterol, LDL cholesterol, non-HDL cholesterol, and cholesterol/HDL ratio than controls. Conclusions . Frequent consumption of red meat, cholesterol, and heme iron rich may contribute to obesity and increased CVR. The low frequency of this consumption, observed in centenarians, although associated with sarcopenia, may be one of the keys to longevity.